Complicated Alcohol Withdrawal—An Unintended Consequence of COVID-19 Lockdown. (13th May 2020) - Narasimha, Venkata Lakshmi; Shukla, Lekhansh; Mukherjee, Diptadhi; Menon, Jayakrishnan; Huddar, Sudheendra; Panda, Udit Kumar; Mahadevan, Jayant; Kandasamy, Arun; Chand, Prabhat K; Benegal, Vivek; Murthy, Pratima
Abstract: Aim: To assess the impact of COVID-19-related lockdown in India on alcohol-dependent persons. Method: We examined the change in the incidence of severe alcohol withdrawal syndrome presenting to hospitals in the city of Bangalore. Results: A changepoint analysis of the time series data (between 01.01.20 to 11.04.20) showed an increase in the average number of cases from 4 to 8 per day (likelihood ratio test: χ 2  = 72, df = 2, P  < 0.001). Conclusion: An unintended consequence of the lockdown was serious illness in some patients with alcohol use disorders.